PREVALENSI BURUH BANGUNAN DENGAN KETERGANTUNGAN NIKOTIN DI KELURAHAN SEMINYAK KECAMATAN KUTA KABUPATEN BADUNG BALI 2013 - Ni Nyoman Mas Utari Rena; I G. K. Nyoman Arijana (E-Jurnal Medika Udayana, 2016)
PREVALENCE OF CONSTRUCTION WORKERS WITH NICOTINE ADDICTION IN SEMINYAK KUTA BADUNG REGENCY BALI 2013 ABSTRACT Background: Smoking behavior is one big common mistake in Indonesian society, both among adolescents and adults. Cigarettes causes addiction, as the result of nicotine compounds inside it. Construction workers is the highest populations that have nicotine dependence. This study aims to know the prevalence of a construction worker with nicotine dependence in the village of Seminyak, Kuta District, Badung regency in 2013. Method: The study involved 35 construction workers who smoked regularly at a hotel project in Double Six Seminyak. Responden given questionnaires: Fargerstrom Test for Nicotine Dependence (FTND) to determine the level of dependence on nicotine. Result: Based on the results of 35 FTND samples, there are 29% who experienced a mild nicotine dependence, 40% had moderate nicotine dependence, and 31% experienced severe nicotine dependence. Conclusion: In this study, there are some drawback, such as the number of samples that can be collected is to small to respesent the whole populaton. So there is a need for further research with more samples and more specific variables, to be used as a guide in its efforts to reduce nicotine dependence in the community, especially the population of construction workers.